2017
DOI: 10.1111/ijfs.13479
|View full text |Cite
|
Sign up to set email alerts
|

Green tea polyphenols reduce obesity in high‐fat diet‐induced mice by modulating intestinal microbiota composition

Abstract: Summary In this study, the modulatory effect of green tea polyphenols (GTP) on human intestinal microbiota was investigated. Firstly, germ‐free mice were inoculated with faecal suspension derived from healthy volunteers to obtain human flora‐associated (HFA) mice model. When the high‐fat diet‐induced obese mice model was successfully established, they were randomly divided into high‐fat diet group (HFD) and high‐fat diet group with GTP (HFD‐GTP), and the shifts in relative abundance of the dominant taxa at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 32 publications
(37 reference statements)
2
32
0
Order By: Relevance
“…The bacteria that can degrade and utilize, or are resistant to, tea polyphenols could flourish and contribute to the overall microbiome shift. Some previous studies showed decreased Firmicutes to Bacteroidetes ratio by green tea polyphenols . In our study, PPE significantly increased the ratio in the intestine, except in cecal mucosa and colonic content (Figure S7, Supporting Information).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The bacteria that can degrade and utilize, or are resistant to, tea polyphenols could flourish and contribute to the overall microbiome shift. Some previous studies showed decreased Firmicutes to Bacteroidetes ratio by green tea polyphenols . In our study, PPE significantly increased the ratio in the intestine, except in cecal mucosa and colonic content (Figure S7, Supporting Information).…”
Section: Discussionsupporting
confidence: 68%
“…Many publications reported that dietary tea polyphenols, at different doses, attenuated body weight gain and decreased the ratio of Firmicutes to Bacteroidetes in mice fed an HFD . It is unclear, however, whether the results were due to the prevention of HFD‐induced changes in microbiota by tea polyphenol treatment, and the role of intestinal microbiota in mediating the beneficial effects of tea, remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…DNA concentrations were measured by a Nano-Drop 1000 spectrophotometer (Thermo Scientific Inc, Wilmington, DE, USA). The V3-V4 region of the bacterial 16S rRNA gene was amplified by PCR using primers 314F (5 0 -CCTACGGGNGGCWGCAG-3 0 ) and 805R (5 0 -GACTA CHVGGGTATCTAATCC-3 0 ) ( Guo et al, 2017). The PCR conditions and reaction mixtures were completed according to methods previously described .…”
Section: Dna Extraction and Illumina Miseq Sequencingmentioning
confidence: 99%
“…Green tea is obtained from Camellia sinensis , which is rich in flavonoids (Omaye & Dubick, ). The main bioactive components in GT are catechins, class of flavonoids and a group of polyphenols (Guo et al, ). The GT catechins are more effective (antioxidant activity) in comparison with other tea polyphenols (Ananingsih, Sharma, & Zhou, ).…”
Section: Introductionmentioning
confidence: 99%